Combined strength and endurance session order: Differences in force production and oygen utake - Taipale, R. S.; Mikkola, J.; Nummela, A. T.; Sorvisto, J.; Nyman, K.; Kyröläinen, H.; Häkkinen, K. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To examine acute responses of force production and oxygen uptake to combined strength (S) and endurance-running (E) loading sessions in which the order of exercises is reversed (ES vs SE). Methods: This crossover study design included recreationally endurance-trained men and women (age 21-45 y; n = 12 men, 10 women) who performed ES and SE loadings. Force production of the lower extremities including countermovement-jump height (CMJ) and maximal isometric strength (MVC) was measured pre-, mid-, and post-ES and -SE, and ground-reaction forces, ground-reaction times, and running economy were measured during E. Results: A significant decrease in CMJ was observed after combined ES and SE in men (4.5% ± 7.0% and 6.6% ± 7.7%, respectively) but not in women (0.2% ± 8.5% and 1.4% ± 7.3% in ES and SE). MVC decreased significantly in both men (20.7% ± 6.1% ES and 19.3% ± 9.4% SE) and women (12.4% ± 9.3% ES and 11.6% ± 12.0% SE). Stride length decreased significantly in ES and SE men, but not in women. No changes were observed in ground-reaction times during running in men or women. Performing S before E caused greater (P < .01) oxygen uptake during running in both men and women than if E was performed before S, although heart rate and blood lactate were similar between ES and SE. Conclusions: Performing S before E increased oxygen uptake during E, which is explained, in part, by a decrease in MVC in both men and women, decreased CMJ and stride length in men, and/or an increase in postexercise oxygen consumption.